Report on the cultural heritage survey for the TAPI Project, Afghanistan: pilot phase EAMENA-ICONEM July 2024 - Rouhani, B; Tarabay, B; Jabri, L; Saroufim. S (EAMENA, School of Archaeology, University of Oxford, 2024)

(untitled)
This report examines the risks posed to Afghanistan's cultural heritage by the TAPI gas pipeline project, focusing on a joint pilot study by the EAMENA project at the University of Oxford and ICONEM. Using remote sensing, 433 heritage sites along the pipeline corridor in Kandahar and Helmand provinces were documented. Among them, 75 are within 500 meters of the pipeline, including qanat irrigation systems crucial for local agriculture. The dataset, following the FAIR principles, is accessible to heritage authorities and researchers, providing a baseline for future monitoring and protection efforts.